Evaluation of preclinical efficacy of human umbilical cord mesenchymal stem cells in ankylosing spondylitis - Shen, Danpeng; Wang, Zhiqiang; Wang, Hongwei; Zhu, Hongyan; Jiang, Cuibao; Xie, Fan; Zhang, Hongpeng; Lv, Qian; Liu, Qi; Qi, Nianmin; Wang, Hao (Frontiers in Immunology, 2023)
Objective: Umbilical cord mesenchymal stem cells (UCMSCs) have significant regenerative, tissue repair, and immunomodulatory properties that can help reduce inflammatory responses in patients with ankylosing spondylitis (AS). In this study, we used a combination of bovine proteoglycan and dimethyldioctadecylammonium (DDA) to establish a mouse model of proteoglycan-induced spondylitis (PGISp). To evaluate the therapeutic effects of UCMSCs, we treated PGISp mice with different doses of hUCMSCs via tail vein injection. Methods: At week 13, the PGISp mice exhibited thickened, erythematous paws, erythema in the extremities, and lameness. CT scans revealed necrotic lysis of chondrocytes, formation of fissures, visible hemorrhage, connective tissue hyperplasia, and focal infiltration of lymphocytes in the intervertebral discs. At week 14, the PGISp mice were randomly divided into three groups and administered different doses of hUCMSCs (0.25, 0.5, and 1.0×107 cells/kg, iv, QOW×2, n=10). To assess the therapeutic effects of hUCMSCs, we evaluated Th cell subsets in the spleen, spleen and thymus coefficients, peripheral blood inflammatory factors, and pathological and imaging observations of the spines and lumbar spines in the PGISp mice. Results: The results demonstrated that injection of hUCMSCs shifted the balance axis between Th1 and Th2 cells in the spleen towards Th2 cells. Moreover, the spleen coefficient and levels of inflammatory cytokines (TNF-α and CCL-2) in the serum decreased after hUCMSC injection. CT imaging and pathological analysis indicated that hUCMSC treatment inhibited ectopic osteogenesis and maintained clear small joint gaps, which slowed down the progression of structural lesions in the disc, nucleus pulposus, fibrous ring, and cartilage in PGISp mice. Conclusion: Administering hUCMSCs at the 14th week after modeling proved to be an effective treatment for PGISp mice. This experiment offers a valuable reference for the pre-clinical use of hUCMSCs in the treatment of AS.